Payback - McNab, Andy.; Rigby, Robert (London : Corgi Books, 2006)
As teenage suicide bombers terrorize England, seventeen-year-old Danny tries to help his grandfather, an ex-SAS explosives expert falsely accused of being a traitorous spy by the government's intelligence agencies.
Young Adult.
Young Adult
Keywords: Great Britain. -- Army. -- Special Air Service -- Fiction; Great Britain. -- Army. -- Special Air Service -- Fiction; Espionage -- Fiction; Grandfathers -- Fiction; Orphans -- Fiction; Spies -- Fiction; Terrorism -- Fiction; Espionage -- Fiction; Grandfathers -- Fiction; Orphans -- Fiction; Spy stories; Terrorism -- Fiction; England -- Fiction; England -- Fiction